The Association of Methotrexate, Sulfasalazine, and Hydroxychloroquine Use With Fracture in Postmenopausal Women With Rheumatoid Arthritis: Findings From the Women's Health Initiative. (18th August 2020) - Carbone, Laura; Vasan, Sowmya; Elam, Rachel; Gupta, Sandeepkumar; Tolaymat, Omar; Crandall, Carolyn; Wactawski‐Wende, Jean; Johnson, Karen C
ABSTRACT: This study was conducted to evaluate the extent to which disease‐modifying antirheumatic medications (DMARDs) used as part of a triple therapy for the treatment of rheumatoid arthritis (RA) including methotrexate, sulfasalazine, and hydroxychloroquine are associated with fractures in postmenopausal women with RA. Incident fractures following use of methotrexate, sulfasalazine, and/or hydroxychloroquine in postmenopausal women with RA in the Women's Health Initiative were estimated by Cox proportional hazards using hazard ratios (HRs) and 95% CIs after consideration of potential confounders. There were 1201 women with RA enrolled in the Women's Health Initiative included in these analyses, of which 74% were white, 17% were black, and 9% were of other or unknown race/ethnicity. Of the women with RA, 421 (35%) had not used methotrexate, sulfasalazine, or hydroxychloroquine, whereas 519 (43%) women had used methotrexate, 83 (7%) sulfasalazine, and 363 (30%) hydroxychloroquine alone or in combination at some time during study follow‐up. Over a median length of 6.46 years of follow‐up, in multivariable adjusted models, no statistically significant association was found between methotrexate (HR, 1.1; 95% CI, 0.8–1.6), sulfasalazine (HR, 0.6; 95% CI, 0.2–1.5), or hydroxychloroquine (HR, 1.0; 95% CI, 0.7–1.5) use and incident fractures or between combination therapy with methotrexate and sulfasalazine or methotrexate and hydroxychloroquine use (HR, 0.9; 95% CI, 0.5–1.6) and incident fractures. In conclusion, postmenopausal women with RA receiving any component of triple therapy should not be expected to have any substantial reduction in fracture risk from use of these DMARDs. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.